The Effect of the Legal Basis of the Unity of the Soul and the Body on the Jurisprudential Fatwa on the Ownership of the Soul over the Body - Gholam Ali Moghadam; Muhammad Mahdi Yazdani Kamarzard (آموزه‌‌های فلسفه اسلامي, 2021)
Fatwās are based on titles and topics. Although the customary attribute (conventionary) prevails over jurisprudential issues; but there are many ways to identify issues, and some issues are based on rational principles, reasoning, analysis, experience, and referring to expert opinions belong to fatwā. The jurist thinks and deduces based on his intellectual foundations, and the philosopher jurist must rule on real subjects based on his foundations in theology, cosmology, or anthropology. Body, limbs and external powers based on the unity of soul and the body that the jurists following the transcendent wisdom are required to do are considered as the hierarchy of the truth of the soul and they are united with it in terms of existence and the body is the appearance of the soul in a natural order (degree), and the ruling of not dominating over the souls will spread to it. Now the question is whether the acceptance of this basis will affect the jurisprudential fatwā related to the issue? In this article, with analytical-example (extensional) method, it is shown how the basis of the unity of soul and body in Islamic wisdom in the jurisprudential issue of soul monarchy has an effect on the body and its subdivisions (extensional, branches) such as amputation, transfer, donation, deprivation of life, etc., and can be considered a new argument for denying domination to members.